2017
DOI: 10.1007/s00702-017-1810-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluid biomarker agreement and interrelation in dementia due to Alzheimer’s disease

Abstract: The cerebrospinal fluid (CSF) levels of β-amyloid 42, total tau, and phosphorylated tau 181 are supposed to be all continuously abnormal in dementia due to Alzheimer's disease (AD), being the most advanced disease stage. The aim of the present study, which included a monocentric and a multicentric sample (N = 119 and 178, respectively), was to investigate the degree of CSF biomarker agreement and interrelation in AD dementia. Based on previously published cut-off values, biomarker values were categorized as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Finally, the clinical diagnosis, which was based on a comprehensive diagnostic procedure and on international diagnostic criteria, was used as the ultimate gold standard. Despite the high validity of the diagnostic criteria for AD, the clinical diagnoses are neither always confirmed at autopsy nor always supported by biomarker constellations typical for AD [39][40][41]. Thus, possibly erroneous clinical assessments should be also taken into account.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, the clinical diagnosis, which was based on a comprehensive diagnostic procedure and on international diagnostic criteria, was used as the ultimate gold standard. Despite the high validity of the diagnostic criteria for AD, the clinical diagnoses are neither always confirmed at autopsy nor always supported by biomarker constellations typical for AD [39][40][41]. Thus, possibly erroneous clinical assessments should be also taken into account.…”
Section: Discussionmentioning
confidence: 98%
“…51 Elevation in CSF p-tau represents the hallmark of tau pathology 5 that has been documented as a good predictor of progression to dementia, 52 but its role as a proxy for cognitive status remains to be defined in AD dementia clinical phenotype. 53…”
Section: Discussionmentioning
confidence: 99%
“…All data reviewed for this study showed that correlation coefficients between cognitive parameters and any CSF biomarker revolve around 0.3 to 0.4 at best, implying that most of the variance defining cognitive impairment remains unclear and is multifactorial, such as the co-occurrence of vascular disease or Lewy body pathology, APOE status, lifestyle parameters, cognitive reserve, among others. 46,53 Hence, in a cohort of patients clinically diagnosed as AD, different factors may collaborate and interact to produce cognitive impairment, which may influence the index of correlation between CSF biomarkers level and cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies conducted in mice have shown long-term persistence and even progression of blast-and impact-induced p-tauopathy [26-28, 33, 34]. In humans, effort has been made to search for an association (or a lack of) between cognitive decline and overlapping neurodegenerative pathologies [35,36], and possible biomarkers that reflect those changes [37]. Repetitive mild TBI was found to be associated with tau pathology and allied neurodegenerative changes in the brain [38].…”
Section: Introductionmentioning
confidence: 99%